Multi-users workstations - Ling, Michael Chee Siang (2015)
The Multi-Users Workstations is special designed for the industry with purpose to minimum the use of the computer on a work place. It also used to improve the computer functionality from a single user to multi-users on one computer on the same time. In order to design a Multi-users workstations for Sati Wealth Consultancy Sdn. Bhd, Rapid Application Development (RAD) has been chosen. RAD has several characteristics that are suitable for the development of Multi-users Workstations. This system is more on configuration to make it work properly. This system was tested with functionality testing, and user acceptance test. The results show the functionality of the system is passed which users satisfy with the system.